Accounting procedures digital transformation for business processes improvement - Yasinska, A. (Видавництво Львівської політехніки, 2021)
The article researches the impact of the digitalization and digital transformation process on the construction of functional management systems of modern enterprises. The article materials consider new information opportunities for business models building and business processes organization. Approaches to the improvement of operational processes and their optimization are substantiated. The evidence is given that the possible way to implement digitalization in certain areas may be: the concept (strategy), staff training and education, the new technologies implementation. It is defined that the implementation of the digital transformation of the business model can take place in stages at the level of its individual elements or components. It is supposed reasonable to use a system-oriented approach to management, which is based on understanding the object of management as a whole, the need for internal and external communication links, i.e., a set of related management methods and tools in the enterprise and its structural units. System-oriented management of the digitalization process in the article is considered to involve the business processes transformation. Such processes should be based on perfect digital strategy planning. Important components are the feasibility assessment of practical digital initiatives implementation, monitoring of promising areas of action, forecasting the expected effect of digitalization and comparison of innovative initiatives. The application of a systematic approach to the management of the digitalization process is justified at certain stages, which will allow in a certain sequence and order to get the maximum effect and ensure the achievement of goals and acceptable results. The main stages of system-oriented management of the business processes digitalization process are offered, as well as the main groups of factors of influence (external and internal) on the digitalization implementation process are determined.
Keywords: system-oriented management; accounting information; digitalization; digitization; business processes; digital transformation; M.11; 657.1